PWE-013 Nutritional care pathways of patients with malignant bowel obstruction: experience from a UK tertiary-referral centre. (June 2019) - Patel, PS; Fragkos, K; Keane, N; Cauldwell, K; O'Hanlon, F; Rogers, J; Obbard, S; Barragry, J; Sebepos-Rogers, G; Mehta, S; Rahman, F; Di Caro, S
Abstract : Introduction: Emerging evidence is gathering for the use of parenteral nutrition (PN) in patients with malignant bowel obstruction (MBO) who have lost nutritional autonomy and developed Intestinal Failure (IF). There is limited evidence describing the outcomes for MBO patients who are not referred for PN. We aimed to examine nutritional care pathways of MBO patients by referral for PN and appropriateness of referral/non-referral for PN. Methods: Retrospective cohort study of adults (≥18yrs) admitted to University College London Hospital, admitted with MBO between 1.1.16- 31.12.16 with any readmissions up to 31.12.17. Data were analysed by comparing patients who were referred (R) and not referred (NR) for PN. Results: 72 patients with 117 MBO admissions (mean±SD age: 63.1±13.1yrs, 79% female), with median no. of admissions/patient: 1 (range: 1–6). 24/72 patients were in R group. Predominant primary malignancies were gynaecological and gastrointestinal (76%). 83% of MBO patients had metastases and 61% were located subdiaphragmatically. All patients were at high risk of malnutrition using UCLH nutrition screening tool (score=8, a score of ≥7 indicates high risk of malnutrition) and mean weight loss on admission was 7%. Discussion of PN at MDT (21 vs. 4%, P=0.02) and dietetic contact (94 vs 41%, P<0.0001) were more likely to occur in the R group. In 13/69 MBO admissions in NR group, the reasons for non-referral to the Nutrition team are unclear. 20/24 referred patients received inpatient PN, and 10 patients went home with PN. The remaining patients did not go home on PN as BO resolved or they were approaching the end of life. There were no differences in weight or BMI by PN referral groups. In all patients, median weight on admission was 55kg (range: 3–00), and 5–5.8kg at 0-3- and 3–6- months follow-up. Overall survival was 4.7 (1.–5.2) months, with no differences by referral groups (figure 1). Conclusion: All MBO patients presented with high risk of malnutrition on admission. Less than half were referred for PN. Patients who received a dietetic review and when PN was discussed at MDT were more likely to be referred for PN. It was unclear in some cases why patients were not referred for PN. This suggest that timing of referral and integration of nutritional care, not just PN, into clinical management discussion at MDT is crucial. Not all patients referred to the Nutrition team were discharged on HPN based on judicious review of each case.